Assessment of knowledge and perspectives of medical students and teachers on physiology electives: a mixed-method survey study in a rural medical college of West Bengal. - Mukherjee, Sanhita; Banerjee , Dr. Goutam; Chakraborty, Ashmita (Student's Journal of Health Research Africa, 2025)
Introduction Elective modules have become a pivotal component of the medical curriculum, enhancing problem-solving skills, self-directed learning, and clinical competence. In India, the National Medical Commission (NMC) introduced electives in 2019 as part of the Competency-Based Undergraduate Curriculum. This study aimed to assess the understanding of medical students and faculty regarding Physiology electives (Electrocardiogram or ECG and Pulmonary function test or PFT) and to evaluate their impact on students’ knowledge acquisition. Methods A mixed-methods study was executed at Rampurhat Government Medical College, West Bengal, involving 30 MBBS students from the 2022 batch who chose either ECG or PFT AS electives. Data collection encompassed pre- and post-tests, Likert-scale-based perception review, and two focused group discussions. Quantitative data were assessed using paired t-tests, and qualitative data were thematically analysed. Results There was a statistically significant advance in post-test scores correlated to pre-test scores in both ECG and PFT groups (p < 0.05), insinuating substantial knowledge gain. Students reported positive discernment, mentioning hands-on clinical exposure, improved diagnostic skills, and optimised communication aptitudes. Faculty reverberated this perspective, acclaiming students ' commitment and the academic utility of the modules. Pivotal limitations included the short duration of the module. Recommended amelioration included extended module duration and more case discussions. Conclusion Physiology electives, when organized, significantly intensify students’ knowledge and clinical readiness. Both students and faculty admitted their educational value. The study supports continued inclusion and expansion of such electives in the undergraduate medical curriculum.